+0  
 
0
292
1
avatar

y=x^0,6-(x-1)^0,6

 

And how do you get the result?

Guest Jun 18, 2017
 #1
avatar+7348 
0

y=x^0,6-(x-1)^0,6

 

Would you like to find the zeros?

 

\(y=f(x)=x^{0.6}-(x-1)^{0.6}=0\)

\(x^{0.6}=(x-1)^{0.6}\)

 

There is no zero.

 

laugh  !

asinus  Jun 18, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.